Outcome of OMG Urethroplasty by Asopa, Barbagli and Kulkarni Technique for Management of Anterior Urethral Stricture : Are Results Affected by the Surgical Technique? - Islam, Md Shariful; Md Asaduzzamman, -; quddus, Md Ruhul; Islam, Waliul; Saha, Pranashis (Bangladesh Journal of Urology, 2020)
Objective: To determine outcome of OMG urethroplasty by different surgical technique comparing ASOPA, BARBAGLI and KULKARNI TECHNIQUE in the management of anterior urethral stricture. Materials and Methods: A total of 62 patients with an average age of 42 yr(21-55) underwent OMG urethroplasty between 2008 to 2015 for anterior urethral stricture of different etiology. 2 patient lost durig follow up patient with lichen sclerosus and failed hypospadias were not included. OMG was always harvested from cheek using 2 team approach graft were placed using surgical technique of ASOPA, BARBAGLI and KULKARNI technique in 21,27 and 12 patients respectively clinical outcome was considered success or failure at the time any post operative procedure needed mean follow up was 45 month (6-95) Results: Out of 60 cases 51(85%) considered success and 9(15%) were considered failure. success rate were 85.7%,85%,and 83.5% in ASOPA, BARBAGLI and KULKARNI Technique and failure rate were 14.3%,15% and 16.7% respectively. Failure involve in the anastomotic site (2 in distal and 3 in proximal) were managed by OIU and involving whole length in 3 patient managed with staged urethropllasty. Conclusion: In our series, success rate of ASOPA, BARBAGLI and KULKARNI technique has no statistically significant variation. more over stricture recurrence was uniformly distributed in all group. so the outcome is not significantly affected by different technique used in OMG urethroplasty for anterior urethral stricture. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.23-27